Experimental and theoretical study on flexural behavior of steel–concrete composite beams strengthened by CFRP plates with unbonded retrofit systems. (1st April 2023) - Qiang, Xuhong; Chen, Longlong; Jiang, Xu
Highlights: CFRP-strengthened steel–concrete composite beams with unbonded reinforcement system were tested. Self-designed prestressing pillars and rotatable end-anchorages were employed to laterally stretch CFRP plate. A theoretical method was proposed to predict the flexural resistance of CFRP-strengthened composite beams. Abstract: In this paper, the flexural behaviors of steel–concrete composite beams strengthened by prestressed carbon fiber-reinforced polymer (CFRP) plate with unbonded retrofit systems were investigated via four-point bending experiments. Three composite beams were strengthened by two groups of CFRP plate with thickness of 2 mm or 3 mm and prestress level of 10 % or 15 %, while one un-strengthened composite beam played a role as reference specimen. CFRP plate was transversely stretched by two scissors-type jacks and fixed on the tension flange of steel girder by an independently designed mechanical anchorage system. The experimental results reveal that the application of prestressed CFRP plate efficiently increased the yielding load and ultimate load of steel–concrete composite beams, but the ultimate deflection of mid-span was little affected. The increase of cross-sectional area of CFRP plates contributes more to stiffness of beams than that of prestress level. The CFRP strength utilization ratios of strengthened beams BS-1 and BS-3 at failure are 80 %, under the condition of proper anchorage. Moreover, the prestress loss of CFRP plate was monitored for about 100 h before test, which was less than 3 %. Furthermore, a theoretical model was proposed to calculate the ultimate flexural resistance of strengthened steel–concrete composite beams with unbonded retrofit systems, which was validated with the experimental results.